An implementation analysis of a Cognitively Guided Instruction (CGI) teacher professional development program - Tazaz, Amanda M.; Schoen, Robert C. (Frontiers in Education, 2023)
Information about program implementation provides critical information for the interpretation of results from randomized trials. The present study provides an evaluation of the implementation of a Cognitively Guided Instruction mathematics teacher professional development as part of a large scale randomized controlled trial with teachers in first- and second- grade in eleven elementary schools in two adjacent school districts. We developed a measure of fidelity of implementation and used it during the in-person training sessions to determine the extent to which the training program was implemented as intended. The results from this study suggest that the program was implemented with high fidelity providing context for interpretation of overall program outcomes on teachers and students.